(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2020)
Free radicals, oxidative stress or antioxidants is more and more often used to explain different pathological disorders and their therapeutic approach. The aim of this study was to evaluate the protective effect of anthocyanin extract obtained by maceration of the flowers of Lavandula dentata in 0.1 % HCl/methanol (v/v) solution on oxidative stress. The antioxidant activity of anthocyanin extract in vitro was evaluated by reduction of iron (FRAP), DPPH and the ß-carotene tests. The in vivo oxidative stress was induced by intraperitoneal injection of 0.5 ml/kg of CCl4 and treated orally by 500mg kg/day of the extract. Anthocyanins extract inhibited the free radical DPPH (IC50:1.3 ± 0.23 mg/ml). Lavender extract prevented the oxidation of B carotene (28.34 ± 0.07%) and has an ability to reduce iron (0.736 ± 0.03). Intraperitoneal injection of CCl4 has increased biochemical parameters, which was evidence of oxidative stress in vivo. In contrast, daily oral administration of anthocyanin extract has restored the biochemical parameters. Histopathological examinations of liver stained with haematoxylin and eosin showed loss of hepatic architecture. These injuries observed have been improved by treatment with anthocyanin extract. The findings revealed that anthocyanin extract from lavender possesses a significant antioxidant activity. Dhaka Univ. J. Pharm. Sci. 19(2): 145-151, 2020 (December)